Penyuluhan Bahaya Judi Online sebagai Upaya Penguatan Ketahanan Rumah Tangga dan Ekonomi Keluarga - Sapri Ali; Nur Fadilah; Ulya Ardhia Cahyani Ahmad; Kafita azzahro; Cindi Devita Sari (LP3M IAIFA Kediri, 2025)
This study aims to analyze and describe the impact of online gambling awareness campaigns on household resilience and the family economy in Balong Jeruk Village, Kunjang District. Online gambling is a disturbing phenomenon with the potential for significant damage, particularly within the family environment. The research employed a qualitative case study approach. Data were collected through in-depth interviews with relevant stakeholders (victims/families, community leaders, and village officials) and participant observation. The results indicate that awareness campaigns regarding the dangers of online gambling remain challenging, although awareness of the risks has begun to develop. The impact of online gambling on household resilience is significant, including increased internal conflict, domestic violence (DV), loss of trust, and even potential divorce. Economically, online gambling practices lead to bankruptcy, significant debt accumulation (including illegal online loan debt), structural poverty within families, and the loss of productive assets. The study's conclusions confirm that online gambling poses a serious threat that undermines the economic and social foundations of families. Synergy between the village government, community leaders, and relevant institutions is needed to strengthen more intensive and comprehensive outreach programs and provide support and rehabilitation mechanisms for victims and their families.